150 years of agricultural education in Guyana : some thoughts and lessons from experience - Davidson, Winslow (Franklin & Franklin Books New YorkUS, 1997)
Describes the curricula and roles of the agencies and institutions that have impacted directly and indirectly upon agricultural education. Suggests reasons why a lesser impact than desired was created and points to improvements that will inform future efforts.